P233 B cell-rich synovitis in early and established rheumatoid arthritis. (20th April 2020) - Rivellese, Felice; Humby, Frances; Bugatti, Serena; Fossati-Jimack, Liliane; Rizvi, Hassan; Lucchesi, Davide; Lliso-Ribera, Gloria; Nerviani, Alessandra; Hands, Rebecca; Giorli, Giovanni; Frias, Barbara; Thornborn, Georgina; et al.
Abstract: Background: The role of B cells in the pathogenesis of rheumatoid arthritis (RA) is well recognised and is confirmed by the established efficacy of B cell depleting treatments. However, B cell infiltration in synovia is highly variable and the association with clinical disease activity has been inconsistently reported, with contradicting results possibly linked to the lack of gold standards for the quantitative and qualitative assessment of B cell synovitis. Here, we aimed at evaluating synovial B cells and their association with clinical phenotype in two large cohorts of patients with early and established RA. Methods: A total of 329 synovial biopsies were obtained from treatment-naïve early-RA (n = 165) and TNF-inhibitor inadequate responders (TNFi-IR) established-RA (n = 164), together with clinical and demographic data. In addition to conventional disease activity scores, 2 component DAS28 CRP (2C−DAS28CRP) was computed as √SJC28 + (0.6×ln (CRP+1)). Upon immunohistochemical staining for CD20, semi-quantitative (Sq) scoring (0-4) was used to classify patients into B cell rich ( ≥ 2) and poor (< 2). B cell area fraction (i.e. percentage of stained tissue) was calculated by automated digital image analysis (DIA) and B cell expression markers were obtained by RNA-sequencing of synovial biopsies from early RA (n = 91) and TNFi-IR patients (127). Results: Semi-quantitative B cell scores positively correlated with the DIA B cell area fraction (Spearman r 0.93 in early RA and 0.88 in TNFi-ir, p < 0.0001) and with RNA-seq B cells signature (Spearman r with CD20 mRNA 0.67, p < 0.0001, with B cell module 0.6, p < 0.0001). B cell-rich synovitis was present in 35% of early RA and 47.1% of TNFi-IR (p = 0.025). Patients with B cell-rich synovitis showed significantly higher synovial inflammatory scores in both cohorts, while differences in disease activity measured by DAS28 and prevalence of autoantibody positivity were only observed in early RA. Interestingly, however, 2C−DAS28CRP was significantly higher in B cell-rich patients both in the early and established RA cohorts. Conclusion: We describe a validated synovial B cell semi-quantitative score that correlates with the quantification of B cells by digital and molecular analyses. Our results also suggest that the imaging-derived 2C−DAS28CRP captures ongoing B cell-rich synovitis both in early and established RA. Disclosures: F. Rivellese None. F. Humby None. S. Bugatti None. L. Fossati-Jimack None. H. Rizvi None. D. Lucchesi None. G. Lliso-Ribera None. A. Nerviani None. R. Hands None. G. Giorli None. B. Frias None. G. Thornborn None. E. Jaworska None. C. John None. K. Goldmann None. M. Lewis None. A. Manzo None. M. Bombardieri None. C. Pitzalis None.